PENGARUH MUSIK KLASIK TERHADAP REGULASI EMOSI TUNADAKSA DI YPAC SURAKARTA - Sugeng Haryadi; Novela Nadia Fardah (Universitas Negeri Makassar, 2015)
Different physical with normal people make children more sensitive physical disability. Physical disability child tends to feel shame, low self-esteem and sometimes appear selfish attitude towards the environment especially when under pressure because of mental disability, failure to manage these emotions can make aggressive and apathetic. The objective of this research was to determine the effect of classical music on emotion regulation physical impairment in YPAC Surakarta. This research is experimental research design using one-group pretest-posttest design. Subjects were physical disability YPAC Surakarta aged 12-16 by 10 students. Methods of data collection in this study using psychological scales are scales of emotion regulation as much as 24 item. Data analysis using statistical testing techniques Non Parametric Wilcoxon Signed Ranks yield sig of 0.025, the value of Z score of -2.809 and a mean rank of 0.00 at pretest posttest whereas at 5.50. It can be concluded that there are changes in emotion regulation significantly between pretest and posttest experimental group after being given treatment in the form of classical music.